El rol de los actores sociales y sus implicancias en la configuración territorial de Moquehue, Neuquén, Argentina - Celia Viviana Torrens; Elsie Marcela Jurio; Vanesa Yanina Cappelletti; Germán Gabriel Pérez; Daiana Elcira Cara Plá; Gimena Nathalie Cuevas; María Silvina Hauw; Pablo Alejandro Leyes (Boletín Geográfico)
Moquehue is a small mountain settlement located in Aluminé department, Neuquén, Argentina. It aroses in the 40's, as a product of the development of cattle raising and forestation. Since these activities began, the permanent settlement and first commercial activities appeared, in order to cover the new demands. Nature has given the region a beautiful landscape that acquires value since the 70's, when the population of nearby localities began to usufruct tourism in the region. Even though the lands belong to the Provincial State, since 1984 they are under the control of the Pulmarí Interstate Corporation (PIC), which regulates their use.